Pengembangan E-Bahan Ajar Berbantuan Augmented Reality Pada Mata Pelajaran IPAS Materi Mengubah Bentuk Energi Untuk Meningkatkan Hasil Belajar Peserta Didik Sekolah Dasar - Lulus Wiji Lestari; Novi Setyasto (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to develop and evaluate the feasibility, practicality, and effectiveness of augmented reality (AR)-based e-learning materials to enhance student learning outcomes. Employing a Research and Development (R&D) approach using the Borg and Gall model, the study involved students from Podorejo 02 Elementary School. Feasibility was assessed through expert validation, which indicated the e-learning materials were "very feasible." Practicality was determined through teacher and student questionnaires, revealing "very positive" satisfaction levels. Effectiveness was demonstrated via a t-test, yielding a significant result (p < 0.05) and a moderate N-gain. The findings confirm that AR-based e-learning materials are feasible, practical, and effective in improving science learning outcomes for elementary school students.